Dietary practices of adolescents during COVID-19 and the perceived effect of the pandemic on nutrition-related behaviours - Ohemeng. A.; Adje. N.A.; Tamakloe. T.; Alhassan. J. (BMC Public Health, 2025)
Background Though there are suggestions on how COVID 19 has affected nutrition-related practices and the nutritional status of people, few studies have evaluated this among adolescents. This study aimed to assess the perceived effect of the pandemic on nutrition-related practices of adolescents. Methods The study was conducted among adolescents (n=290) in three Metropolitan, Municipal, and District Assemblies (MMDAs) in Accra using a cross-sectional design. Participants provided information on dietary habits, and diet-related messages received during the pandemic. Food consumption during the peak periods of COVID-19 and afterwards was assessed using a 7-day food frequency tool. Food consumption scores (FCS) were generated based on the guidelines of the World Food Programme. The dietary practices of the participants at the two time periods (during and after pandemic) were compared using Pearson’s Chi Square tests. Results While meal frequency remained similar during and after the peak of the COVID-19 pandemic among the participants, meal skipping and dependence on ready-to-use foods were significantly lower during the peak of the COVID pandemic. Though significantly higher proportions of the participants consumed legumes/nuts/seeds and sugar-sweetened beverages (SSB) at the peak of the pandemic compared to afterwards, overall food consumption was similar at the two time points (acceptable diet: 100% vs. 99.3%). More than a third of the study participants indicated that COVID-19 had negatively affected their food quantity, exercise, and overall physical activity level. Additionally, 41% indicated that their screen time increased at the same time. Conclusion Our study found that food consumption among adolescents in Accra did not vary much with respect to the COVID-19 pandemic. However, the observed high intake of SSBs coupled with reduced physical activity levels call for concerted efforts from various stakeholders to address these habits to avoid an even faster increasing rate of obesity
Research Article
Keywords: Adolescents; COVID-19; Nutrition-related practices